2001
DOI: 10.1021/jo001380+
|View full text |Cite
|
Sign up to set email alerts
|

Bengamides Revisited:  New Structures and Antitumor Studies

Abstract: The structural chemistry and biological activity of the bengamide class of compounds have been further characterized. Extracts prepared from recollected Jaspis cf. coriacea from five sites in Fiji were pooled. Six new bengamides, M (7b), N (8a), O (8b), P (9a), Q (9b), and R (10), were identified, accompanied by the known bengamides A (1a), B (1b), E (3a), F (3b), Y (5), Z (6), L (7a), G (11a), H (11b), and I (12). The structures of the new compounds were determined from spectroscopic data, and some were addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 23 publications
3
65
0
Order By: Relevance
“…However, despite the lack of specificity in vitro, tumor-specific activity was seen with bengamides in vivo, as demonstrated by the striking antitumor activity in xenograft models at well tolerated doses (3). In additional studies comparing more frequent dosing, LAF389 has been observed to result in tumor regression, 2 an effect more pronounced than the in vivo responses reported with a potent fumagillin analogue, TNP-470, which gave at most cytostatic activity in human tumor xenograft models (27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, despite the lack of specificity in vitro, tumor-specific activity was seen with bengamides in vivo, as demonstrated by the striking antitumor activity in xenograft models at well tolerated doses (3). In additional studies comparing more frequent dosing, LAF389 has been observed to result in tumor regression, 2 an effect more pronounced than the in vivo responses reported with a potent fumagillin analogue, TNP-470, which gave at most cytostatic activity in human tumor xenograft models (27).…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of the assignment of the N-terminal sequences was performed by nano-ESMS/MS sequencing. Direct selection of the triply charged parent ion at m/z 421.22 from the Lys-C digest of the induced 14-3-3␥ isoform and subsequent fragmentation produced sufficient y and b type fragment ions to identify unambiguously the sequence of the peptide as M(oxi)-VDREQLVQK (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). A similar analysis of the aminoterminal peptide of the tryptic digest of the constitutive 14-3-3␥ confirmed the complete sequence as acetyl-VDREQLVQK (2-10) (data not shown).…”
Section: A Proteomics Approach Identifies An Alteration In a 14-3-3mentioning
confidence: 99%
See 2 more Smart Citations
“…Sponges of the genus Jaspis are reported to contain many biologically active molecules, which include macrolides [jaspisamides (Kobayashi et al, 1993)], cyclic peptides [jaspamides (Gala et al, 2007) or jasplakinolide (Crews et al, 1986)], amino acid derivatives [bengamides (Thale et al, 2001) and bengazoles (Groweiss et al, 1999)], and triterpenes (Tang et al, 2006). Similarly, macrolide lactams [poecillastrins (Takada et al, 2007)] and sesquiterpene derivatives (Killday et al, 1993) have been isolated from sponges of the genus Poecillastra.…”
Section: Introductionmentioning
confidence: 99%